First report of baby crab molecular identification from the North Coast of Cirebon, Indonesia - Achmad Mufidh Karohmatullah; Aninditia Sabdaningsih; Suradi Wijaya Saputra; Fitria Sari (Depik, 2024)
Baby crab consumption has become a growing trend in snack markets across Asia, with rising popularity in at least five countries. Cirebon, situated on the coast of West Java, is a region experiencing particularly high demand for baby crab commodities, notably the locally known "kroyo" crab. However, without adequate information on this species, its future stock sustainability may be compromised. Indonesian regulations governing high-value Crustacea commodities, outlined in Ministry of Marine Affairs and Fisheries Regulation Number 16 of 2022, include lobster (Panulirus spp.), mangrove crab (Scylla spp.), and blue swimming crab (Portunus spp.). This study employs both morphological and molecular analyses, utilizing DNA barcoding techniques. Male (AMJ) and female (AMB) crabs were collected in February 2023 from Gebang Waters, Cirebon, Indonesia. Morphological identification followed guidelines established by the Food and Agriculture Organization (FAO) for crabs, while molecular identification utilized the Cytochrome Oxidase I (COI) gene. Morphological features such as carapace characteristics, front-orbital border, and cheliped spine morphology categorize the specimens under the genus Charybdis. Specifically, the presence of two spines in the cheliped indicates classification as Charybdis anisodon, a conclusion supported by molecular analysis revealing a 98.9298.96% similarity with C. anisodon. Further analysis of the stock of this crab species is necessary to enhance awareness of its exploitation and inform sustainable management practices.Keywords:Baby crabDNA barcodingFisheries managementIdentificationMorphological